Recepcja mitu o córkach Minyasa w powieści "Frenzy" Percivala Everetta - Wesołowska, Monika (Collectanea Philologica, 2021)
This paper deals with the myth of Minyas’ daughters in the novel Frenzy by Percival Everett, a Distinguished Professor of English at the University of Southern California. He has brought forward a new interpretation of that myth in his book. The main theme is the story of god Dionysus based on Euripides’ Bacchae to which the author adds other mythes. References to Ovid, Aelian and Antoninus Liberalis can also be found.